A 13.5‐in. Quad‐FHD flexible CAAC‐OS AMOLED display with long‐life OLED device structure. Issue 12 (25th May 2015) - Uesaka, Shogo; Yamaoka, Ryohei; Sasaki, Toshiki; Chida, Akihiro; Kawashima, Susumu; Isa, Toshiyuki; Seo, Satoshi; Hirakata, Yoshiharu; Yatsuzuka, Shota; Ohide, Takayuki; Nakada, Masataka; Yamazaki, Shunpei; et al.
Abstract In this study, the device structure of a white tandem organic light‐emitting diode (OLED) was changed to control the emission area and thereby achieve less luminance decay. A long‐life 13.5‐inch 4 K flexible c‐axis‐aligned crystal oxide semiconductor (CAAC‐OS) active‐matrix OLED with less color shift and high resolution was fabricated using this long‐life white OLED, transfer technology, and a CAAC‐OS field‐effect transistor.